"There's a problem, now what's the solution?": suggestions for technologies to support the menopausal transition from individuals experiencing menopause and healthcare practitioners. (12th February 2021) - Backonja, Uba; Taylor-Swanson, Lisa; Miller, Andrew D; Jung, Se-Hee; Haldar, Shefali; Woods, Nancy Fugate
Abstract: Objective: To elicit novel ideas for informatics solutions to support individuals through the menopausal transition. (Note: We use " individuals experiencing menopause " and " experiences " rather than " symptoms " when possible to counter typical framing of menopause as a cisgender women's medical problem.) Methods: A participatory design study was conducted 2015–2017 in the Western US. Two sessions were held with individuals experiencing menopause recruited from the general public; and 3 sessions with healthcare practitioners (HCPs) including nurses, physicians, and complementary and integrative health (CIH) practitioners were held. Participants designed technologies addressing informational needs and burdensome experiences. HCPs reflected on designs from participants experiencing menopause. Directed content analysis was used to analyze transcripts. Results: Eight individuals experiencing menopause (n = 4 each session) and 18 HCPs (n = 10 CIH, n = 3 nurses, n = 5 physicians) participated. All participants provided ideas for solution purpose, hardware, software, features and functions, and data types. Individuals experiencing menopause designed technologies to help understand and prevent burdensome menopause experiences. HCPs designed technologies for tracking and facilitating communication. Compared to nurses and physicians, CIH practitioners suggested designs reframing menopause as a positive experience and accounted for the complex lives of individuals experiencing menopause, including stigma; these ideas corresponded to comments made by participants experiencing menopause. Participants from both populations were concerned about data confidentiality and technology accessibility. Conclusions: Participant generated design ideas included novel ideas and incorporated existing technologies. This study can inform the development of new technologies or repurposing of existing technologies to support individuals through the menopausal transition.